2015
DOI: 10.1242/dev.114322
|View full text |Cite
|
Sign up to set email alerts
|

Late Alk4/5/7 signaling is required for anterior skeletal patterning in sea urchin embryos

Abstract: Skeletal patterning in the sea urchin embryo requires a conversation between the skeletogenic primary mesenchyme cells (PMCs) and the overlying pattern-dictating ectoderm; however, our understanding of the molecular basis for this process remains incomplete. Here, we show that TGF-β-receptor signaling is required during gastrulation to pattern the anterior skeleton. To block TGF-β signaling, we used SB431542 (SB43), a specific inhibitor of the TGF-β type I receptor Alk4/5/7. Treatment with SB43 during gastrula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 56 publications
(94 reference statements)
3
53
0
Order By: Relevance
“…This is an unexpected result, since the known ectodermal Tbx2/3 inducers are dorsal genes or signals (Su et al, 2009;Saudemont et al, 2010); however, little is known about the regulation of PMC-specific Tbx2/3 expression. We note that inhibition of ventral specification in L. variegatus embryos results in radial Tbx2/3 expression (data herein and Piacentino et al, 2015), suggesting that ventral signals locally suppress Tbx2/3 expression, which is otherwise globally induced.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This is an unexpected result, since the known ectodermal Tbx2/3 inducers are dorsal genes or signals (Su et al, 2009;Saudemont et al, 2010); however, little is known about the regulation of PMC-specific Tbx2/3 expression. We note that inhibition of ventral specification in L. variegatus embryos results in radial Tbx2/3 expression (data herein and Piacentino et al, 2015), suggesting that ventral signals locally suppress Tbx2/3 expression, which is otherwise globally induced.…”
Section: Discussionsupporting
confidence: 55%
“…Previous work showed that sulfated proteoglycans regulate DV specification in sea urchin embryos (Bergeron et al, 2011) and consistent with those results, we found that removal of sulfur or addition of chlorate to early embryos perturbed the DV axis (not shown). To avoid this, we began each treatment at 10 h post fertilization (hpf ), after the DV axis is established, but before PMC ingression and migration (Bradham and McClay, 2006;Piacentino et al, 2015). Both treatments provoked uniformly low SPG levels, similar to results with SLC MO (Fig.…”
Section: Sb and Nickel Have Opposite Effects On Ectodermal Specificatmentioning
confidence: 63%
See 3 more Smart Citations